Work Motivation Mediates the Effect Of Work Stress On Employee Performance At PT. Tiki Jalur Nugraha Ekakurir (JNE) South Denpasar - Cyntia Lukyta Sari; Ida Bagus Ketut Surya (International Journal of Economics, Commerce, and Management, 2025)
This study aims to examine the mediating role of work motivation on the effect of work stress on employee performance. The sample consisted of 140 employees selected using purposive sampling technique. Data were collected through questionnaire distribution. The data analysis technique employed in this study was Structural Equation Modeling (SEM) based on variance or component-based SEM known as Partial Least Squares (PLS). The results indicate that work stress has a negative and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Work stress has a negative and significant effect on work motivation. Furthermore, work motivation mediates the effect of work stress on employee performance. Theoretically, the findings support previous research through the lens of Self-Determination Theory. Practically, the results provide valuable insights for companies to manage work stress effectively in order to improve employee performance and to enhance employee work motivation.